Accelerated epithelium-on or accelerated epithelium-off corneal collagen cross-linking: Contralateral comparison study - Yüksel, Erdem; Yalçin, Nuri̇ye Gökçen; Çubuk, Mehmet Özgür (Medknow, 2020)
The aim of the study is to compare the accelerated epithelial-on corneal collagen cross-linking (epi-on CXL) and accelerated epithelial-off corneal collagen cross-linking (epi-off CXL) in terms of clinical and confocal microscopy results.Forty-two eyes of 21 patients with progressive keratoconus and simultaneously undergoing accelerated epi-on CXL in one eye and accelerated epi-off CXL in other eye were evaluated. Uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) with spectacle in logMAR and topographic findings (mean keratometry [K mean] and maximum keratometry [Kmax]) were recorded at 1, 3, 6, 12, 18, 24, and 30 months. Eyes were compared in terms of subjective pain scores after the procedures. Furthermore, anterior segment optical coherence tomography and confocal microscopy were performed at 1 month.Kmean and Kmax were less than baseline in both the groups; however, the reduction was significantly higher in epi-off CXL than epi-on CXL eyes at 18 and 30 months. The UCVA and BCVA increased approximately 1 Snellen line at the end of mean follow-up in epi-off CXL and in epi-on CXL. Stromal demarcation line for epi-off CXL is 276.4 ± 58.9 while 148.3 ± 24.8 for epi-on CXL (P = 0.001). Furthermore, subepithelial nerves were observed in any eye in epi-off CXL; however, subepithelial nerves were observed in 12 eyes (80%), in epi-on CXL (P = 0.01).Both techniques were able to stop progression; however, in contrast to expectations, the pain was felt more in epi-on CXL than epi-off CXL.
Keywords: Ophthalmology; keratoconus; epithelium-off corneal collagen cross-linking; transepithelial corneal collagen cross-linking; Original Article; RE1-994